Multistage Bilevel Planning Model of Energy Storage System in Urban Power Grid Considering Network Reconfiguration - Cai, Zhongqi; Yang, Kun; Chen, Yong; Yang, Ruixiong; Gu, Yanxun; Zeng, Yu; Zhang, Xi; Sun, Sashuang; Pan, Sirong; Liu, Youbo; Liu, Junyong (Frontiers in Energy Research, 2022)
The large-scale integration of renewable energy sources (RESs) and the rapid development of loads cause frequent transmission congestion in urban power grid (UPG). Transmission system operators usually perform the high voltage distribution network (HVDN) reconfiguration to mitigate the transmission congestion. However, as the loads and RES change rapidly, the HVDN reconfiguration might be conducted frequently. This might cause severe security problem. Energy storage system (ESS) provides an effective way of alleviating the transmission congestion. If the ESS is installed and operated elaborately, the transmission congestion of UPG can be mitigated with a little HVDN reconfiguration. Hence, this paper proposes a multi-stage bi-level planning model for the optimal allocation of ESS. The upper-level model aims at maximizing the annual comprehensive revenue of HVDN and the lower-level model focuses on the minimization of the operational cost. Simulation results carried out on a real-world test system verify that the proposed method has the great potential of reducing the investment and operational cost while mitigating the transmission congestion.